Nonpathogenic Fusarium oxysporum endophytes provide field control of nematodes, improving yield of banana (Musa sp.) - Waweru, B.W.; Turoop, L.; Kahangi, E.; Coyne, Danny L.; Dubois, T. (Elsevier, 2014)
Endophytic colonization by the fungus Fusarium oxysporum can result in increased host resistance topests and diseases, and greater biomass production. However, few studies have assessed the field performanceof this fungus for biological control of pests and diseases in banana. Further to greenhouse assessment,studies were carried out to evaluate the performance of F. oxysporum strains against plant-parasiticnematodes on banana (Musa sp., cv. Giant Cavendish and cv. Grand Nain) in the field using tissue-culturedplants. Plants were inoculated separately with one of three strains (V5W2, Eny 7.11o and Emb 2.4o)before being inoculated with Pratylenchus goodeyi and Helicotylenchus multicinctus in an on-station trialand in an on-farm trial planted in a field naturally infested with the same nematodes. All three endophyticstrains significantly suppressed P. goodeyi and H. multicinctus densities and damage in the field.On-station, nematode population densities were reduced by >45% in endophyte-inoculated plants comparedto non-inoculated plants, while percentage root necrosis was reduced by >20%. Similarly, on-farm,nematode damage to roots and densities were also significantly lower in endophyte-inoculated plantscompared with control plants. Significantly improved yields were observed for plants inoculated withendophytes when compared to the control plants, with inoculation with strains Emb 2.4o and V5W2resulting in up to 35% and 36% increased banana yields, respectively, for the on-station trial. For theon-farm trial, up to 20% increase in yields were observed for strain Eny 7.11o compared to control plants.This study provides the first report from the field in Africa on the reduction of nematode populations anddamage, and the increase in banana production by fungal endophytes. The study shows that endophyteshave potential to enhance yields of tissue-cultured banana plants and protect them against pests.